Oral Health Status and Treatment Needs of School Teachers in Kathmandu District - Khanal, Sunita; Shrestha, Sujita (Journal of Nepalese Society of Periodontology and Oral Implantology, 2023)
Introduction: Oral health is an integral part of general health. The high prevalence of dental diseases and conditions like dental caries, periodontitis, and malocclusion may lead to absenteeism from work as well as economic loss. Objective: To assess the oral health status and treatment needs of school teachers in Kathmandu district. Methods: An analytical cross-sectional study was conducted from January-June 2022 among the school teachers of Kathmandu after getting approval from the institutional review board of Kantipur Dental College. Informed consent was also obtained before the study. Data was entered in Microsoft Excel and analyzed using SPSS version 20. P value˂ 0.05 was considered statistically significant. Results: A total of 165 teachers participated in the study out of which 125 (75.80%) were females and 40 (24.20%) were males with a mean age of 36.29±10 were there. The prevalence of dental caries was 98 (59.40%), gingivitis138 (83.60%), periodontal pocket 40 (24.20%), and 39 (23.60%) had 4-5 mm pocket but only 1 (0.60%) had more than 6mm pocket, 2 (1.20%) had upper and 14 (8.50%) had lower dentures. There was no significant difference in dental caries and periodontal status among the government and private school teachers (p=0.081), (p=0.101) respectively but a significant difference in gingivitis status (p=0.001) Conclusion: The oral health status of the teachers was not satisfactory since there was a high prevalence of dental diseases. So, it can be improved by periodically conducting oral health education programs at schools and motivating them